TANGGUNG JAWAB LESSEE TERHADAP MUSNAHNYA BARANG MODAL KARENA KEADAAN MEMAKSA (FORCE MAJEURE) DALAM PERJANJIAN LEASING - Agus Adi Mahardika, I Made; Mertha, I Ketut (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Leasing is a form of business which is used as an alternative to overcome the difficulties experienced by the capital that entrepreneurs and entrepreneurial individuals who are members of a legal entity. However, a problem not uncommon in the lease agreement, among which are the responsibility of the Lessee to the destruction of capital goods due to circumstances that force (force majeure). Therefore, in this paper will discuss whether the Lesse be prosecuted in terms of the destruction of capital goods because circumstances force (force majeure) by the lessee and whether efforts to be made by the lessor to anticipate problems in the case of capital goods destroyed because circumstances force (force majeure) the lease agreement.
Keywords: Responsibility, Capital Goods, Force Condition, Leasing Agreements